PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU MANAJEMEN KEUANGAN MAHASISWA (Survey pada Mahasiswa Jurusan Pendidikan Ekonomi Universitas Siliwangi Angkatan 2021) - Ditya Nurul Fauziyah; Ai Nur Solihat; Kurniawan Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This reseacrh was motivated by the idea that university students should ideally understand financial literacy, which can positively impact their financial management behavior. Healthy financial management behavior can be seen in activities related to financial planning, management, and effective financial control. Student lifestyles also influence their financial management behavior. Lifestyle is defined as an individual’s way of life, encompassing consumption habits, spending priorities, and interests. This study aims to examine the influence of financial literacy and lifestyle on students' financial management behavior. The research uses a quantitative method with an inferential approach. Data collection was conducted thgough surveys. The population of this research consistes of students from the 2021 Economics Education Program at Siliwangii University, with a saturated sampling technique resulting in a sample size of 106 respondents. The findings indicate a positive and significant effect, supported by simultaneous testing showing t calculated > t Table 18.521 > 3.08. This indicates that both financial literacy and lifestyle significantly influence the financial management behaviors of students. Consequently, it can be concluded that financial literacy and lifestyle can enhance the financial management behaviors of university students.